Formation of protective Cr2O3 scale at high temperature and the effect of mass transport in the presence of water vapor - Ani, Mohd Hanafi; Othman, Raihan (Trans Tech Publications Ltd., Switzerland, 2012)
The formation of protective Cr2O3 scale at high temperature was evaluated using Wagner’s theory of binary alloy oxidation. The results show that at 1073 K, around 9.8 wt% of Cr is required to form external Cr2O3 scale, and 3.5wt% of Cr is needed to maintain the scale. Introduction of water vapor has shifted the critical Cr concentration to higher value. The effects of water vapor in increasing Cr critical concentration to form external Cr2O3 scale was disscussed from view of oxygen permeablility and Cr diffusivity in the alloy. It is concluded that Cr diffusivity has negligible effect, while oxygen permeability increase with the presence of water vapor, thus increase the oxidation rate.